Water Fire saga, Deep blue - Donnelly, Jennifer (Disney-Hyperion, 2014)
Uncovering an ancient evil, Serafina, a mermaid of the Mediterranean Sea, searches for five other mermaid heroines who are scattered across the six seas, to save their hidden world.
Keywords: Mermaids -- Fiction; Supernatural -- Fiction; Magic -- Fiction; Good and evil -- Fiction